PENGARUH MODEL PEMBELAJARAN AKTIF TYPE QUIZ TEAM TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Maulidiawati Maulidiawati; Murtafiah Murtafiah; Nenny Indrawati (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine whether there is a significant effect of the application of the Quis Team type active learning model on the mathematical problem solving ability of students in class XII IPA at SMA Negeri 1 Sendana. This research uses experimental research and Quasi Experimental Design. The population in this study was 98 students. Sampling was determined by using simple random sampling where students of class XII IPA 1 were selected as the experimental class and students of class XII IPA 3 were selected as the control class. The data were collected by the learning implementation observation sheet instrument and the test instrument in the form of pre-test and post-test. Furthermore, the data of this study were analyzed with descriptive statistics and inferential statistics using a significance level of 0.05. The results of the hypothesis test indicate that there is a significant influence on the application of the Quis Team type active learning model on math problem solving skills in high school